Optoacoustic biomarkers of lipids, hemorrhage and inflammation in carotid atherosclerosis - Karlas, Angelos; Fasoula, Nikolina-Alexia; Kallmayer, Michael; Schäffer, Christoph; Angelis, Georgios; Katsouli, Nikoletta; Reidl, Mario; Duelmer, Felix; Al Adem, Kenana; Hadjileontiadis, Leontios; Eckstein, Hans-Henning; Ntziachristos, Vasilis (Frontiers in Cardiovascular Medicine, 2023)
Imaging plays a critical role in exploring the pathophysiology and enabling the diagnostics and therapy assessment in carotid artery disease. Ultrasonography, computed tomography, magnetic resonance imaging and nuclear medicine techniques have been used to extract of known characteristics of plaque vulnerability, such as inflammation, intraplaque hemorrhage and high lipid content. Despite the plethora of available techniques, there is still a need for new modalities to better characterize the plaque and provide novel biomarkers that might help to detect the vulnerable plaque early enough and before a stroke occurs. Optoacoustics, by providing a multiscale characterization of the morphology and pathophysiology of the plaque could offer such an option. By visualizing endogenous (e.g., hemoglobin, lipids) and exogenous (e.g., injected dyes) chromophores, optoacoustic technologies have shown great capability in imaging lipids, hemoglobin and inflammation in different applications and settings. Herein, we provide an overview of the main optoacoustic systems and scales of detail that enable imaging of carotid plaques in vitro, in small animals and humans. Finally, we discuss the limitations of this novel set of techniques while investigating their potential to enable a deeper understanding of carotid plaque pathophysiology and possibly improve the diagnostics in future patients with carotid artery disease.